2016
DOI: 10.1080/23279095.2016.1243108
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment (MoCA) as a screening test for cognitive dysfunction in multiple sclerosis

Abstract: Conclusions: The MoCA is a useful and sensitive instrument to identify the MS-related cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 58 publications
3
31
0
1
Order By: Relevance
“…The present study showed that MS patients have a statistically significant higher MFIS score (physical, cognitive, and psychosocial) and a statistically significant low MoCA score than the controlled group. This finding met with those of Pellicano and colleagues ( 2010 ) and Freitas and colleagues ( 2018 ) respectively.…”
Section: Discussionsupporting
confidence: 84%
“…The present study showed that MS patients have a statistically significant higher MFIS score (physical, cognitive, and psychosocial) and a statistically significant low MoCA score than the controlled group. This finding met with those of Pellicano and colleagues ( 2010 ) and Freitas and colleagues ( 2018 ) respectively.…”
Section: Discussionsupporting
confidence: 84%
“…We used the same battery as in Serino et colleagues 19 : global cognitive level was assessed with the Montreal Cognitive Assessment (MoCA) 28 – which has been shown to be sensitive in identifying MS-related cognitive impairment 29 ; executive functioning was assessed using the Trail Making Test 30 (in two specific sub-tests: TMT-A and TMT-B) as a visuo-spatial examination with an index of time; PIT 360°; and a measure of phonemic verbal fluency, the controlled oral word association test (FAS form) 23 .…”
Section: Methodsmentioning
confidence: 99%
“…The Montreal Cognitive Assessment (MoCA) is a sensitive and reliable 10-minute cognitive screening test. 35, 36 It has been used successfully as a screening tool for cognitive impairment in MS. 36 Higher scores indicated better performance and a score ≥26 out of 30 is considered normal.…”
Section: Methodsmentioning
confidence: 99%